Strategi Kepemimpinan Bersama (Shared Leadershep) Sebagai Peningkatan Mutu Sekolah - Gusdil Wahyuni , Lisa; Syevyilni Wisda , Rini (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
This research aims to understand the role of joint leadership as a strategy in improving the quality of education in schools. The focus of this research is to examine the views of the principal, vice principal, and teachers at Attayibah Kerinci Junior High School through a qualitative narrative approach. The data analysis method used refers to Miles and Huberman (1994), including data reduction, data presentation, and conclusion drawn. The results of the study show that co-leadership is able to increase active participation, a sense of belonging, and collaboration in the school community. This positive impact contributes to improving the quality of learning and school management. This research provides practical insights for stakeholders in designing effective leadership strategies to improve the quality of education. Data from UNESCO (2023) shows that around 20% of schools in rural areas of Indonesia experience resource limitations and low community participation, which hinders the improvement of education quality. This research seeks to fill the gap by highlighting the role of collaboration as a solution in building a more active and organized school community